PENERAPAN METODE EXTREME PROGRAMMING PADA SISTEM INFORMASI PENJUALAN BERBASIS WEB - Ardhana, Valian Yoga Pudya (Journal of Information Systems Management and Digital Business, 2024)
Along with the development of the industrial revolution 4.0, the need for fast and accurate information is increasing. Sales information systems are needed for business actors operating in various business fields. Especially for business actors whose sales are increasing over time. The increasing number of consumers often becomes an obstacle for business actors in providing product sales services to consumers. This research carried out the development of a sales information system using the extreme programming method approach. The extreme programming approach is able to develop applications relatively quickly and produce applications that suit your needs. This web-based sales information system has the features that business people need to run their business effectively and efficiently. Apart from that, the test results using black-box testing produced a score of 100%, this means that the features contained in the application meet your needs.